The Pulmonary Microbiota: Mediation of Lung Pathogenesis and a Possible Therapeutic Target in Patients with Asthma - Greer, Spencer; Johnson, Caleb; Work, Parker; Button, Nadja Vawryk; Karaduta, Oleg (Current Probiotics, 2024)
Traditional views of a sterile lung environment have been revised with the recognition of a complex pulmonary microbiome. The interaction of this microbiota with host immune responses plays a pivotal role in the pathogenesis of various respiratory diseases, including asthma. This review aims to explore the impact of the pulmonary microbiota on asthma development and assess the potential of probiotics as a therapeutic intervention. A mini-review was conducted in accordance with JBI methodology, focusing on studies that compared asthmatic patients with controls in terms of pulmonary microbiome composition. The primary sources were extracted and synthesized using JBI SUMARI, emphasizing studies involving probiotic interventions. Significant differences in the pulmonary microbiome between asthmatics and healthy individuals were noted, with dominant genera, such as Haemophilus and Moraxella linked to inflammation and asthma severity. Importantly, preliminary studies suggest that probiotics may influence these microbial communities, potentially reducing inflammatory responses and improving asthma outcomes. The findings indicate a robust link between the pulmonary microbiome and asthma pathogenesis, with probiotics offering a promising avenue for modulating this interaction. The modulation of the lung microbiome through probiotics could represent a novel therapeutic pathway, potentially decreasing asthma severity by restoring microbial balance and enhancing immune homeostasis. This review underscores the critical role of the pulmonary microbiome in asthma and highlights the innovative potential of probiotic treatments. Future research should focus on clinical trials to verify the efficacy of probiotics in managing asthma, aiming to establish a new paradigm in therapeutic strategies.
Keywords: immune homeostasis